β-Amyloid Plaque Reduction in the Hippocampus After Focused Ultrasound-Induced Blood–Brain Barrier Opening in Alzheimer’s Disease - D’Haese, Pierre-François; Ranjan, Manish; Song, Alexander; Haut, Marc W.; Carpenter, Jeffrey; Dieb, Gerard; Najib, Umer; Wang, Peng; Mehta, Rashi I.; Chazen, J. Levi; Hodder, Sally; Claassen, Daniel; et al. (Frontiers in Human Neuroscience, 2020)
The blood–brain barrier (BBB) limits therapeutic delivery in Alzheimer’s disease (AD) and other neurological disorders. Animal models have demonstrated safe BBB opening and reduction in β-amyloid plaque with focused ultrasound (FUS). We recently demonstrated the feasibility, safety, and reversibility of FUS-induced BBB opening in the hippocampus and entorhinal cortex in six participants with early AD. We now report the effect of BBB opening with FUS treatment on β-amyloid plaque. Six participants underwent 18F-Florbetaben PET scan at baseline and 1 week after the completion of the third FUS treatment (60 days interval). PET analysis comparing the hippocampus and entorhinal cortex in the treated and untreated hemispheres revealed a decrease in the ratio of 18F-Florbetaben ligand binding. The standard uptake value ratios (SUVr) reduction ranged from 2.7% to 10% with an average of 5.05% (±2.76) suggesting a decrease in β-amyloid plaque.